Efisiensi Pelaksanaan Tank Cleaning untuk Menunjang Kesiapan Muat di MT. Savir Tiger - Andreas Victor Pagengga (MASALIQ, 2026)
Tank cleaning is an essential operation on tankers to ensure cargo tank readiness, particularly after transporting cargoes that leave persistent residues and may contaminate subsequent cargoes. This study aimed to analyze the implementation of tank cleaning on MT. Savir Tiger, identify the factors causing delays in its completion, and formulate operational improvements to support loading readiness. The study employed a qualitative descriptive approach with a case study design conducted on MT. Savir Tiger during sea practice from February 8, 2024, to May 21, 2025, with observations focusing on the transition from fuel oil to gasoil cargoes during July–August 2024. Data were collected through direct observation, informal interviews with officers and deck crew, and documentation of ship particulars, tank-cleaning equipment, checklists, and cleaning procedures. The data were analyzed through data reduction, data display, and conclusion drawing by applying source triangulation. The findings showed that tank cleaning was conducted through the stages of pre-cleaning, chemical cleaning, rinsing, flushing, draining, drying, mopping, and final inspection. However, its efficiency was hindered by damage to the fixed Butterworth equipment and hose nozzles, limited ventilation during work in enclosed spaces, incomplete flushing and mopping, weak stage-by-stage supervision, and the re-entry of residual water due to leaking valves. Although 24 days were available during the voyage and anchorage period for cleaning and demucking, the surveyor’s inspection still identified residues, requiring recleaning before loading. This study concludes that tank cleaning needs to be managed as an integrated loading-readiness control system by improving equipment reliability, procedural compliance, occupational safety in enclosed spaces, inspection at every stage, and evidence-based documentation to minimize contamination and improve tanker operational efficiency.